STUDI POTENSI EKOWISATA MANGROVE DI PETENGORAN, KABUPATEN PESAWARAN - Cesarani, Anisa; Herison, Ahmad; Ashruri, Ashruri; Romdania, Yuda (Universitas Lampung, 2023)
Mangrove ecotourism is difficult to establish. This is caused by the lack of awareness of the community and village officials in managing these tourist attractions. Activities to develop the Petengoran mangrove ecotourism area to improve the welfare of coastal communities through the preparation of guidelines for the development of mangrove ecotourism for stakeholders from Gebang Village. So this study aims to determine the type, density value, frequency, dominance and important index value (INP) of the Petetengoran mangrove by collecting data using the line transect method by counting the number of species (trees, poles, saplings, seedlings). From the research results with 3 observation plots, four species were found, namely: Avicennia Marina, Ceriops Sp, Rhizophora Apiculata, Rhizophora Stylosa. The type of mangrove that has the highest important value index (INP) for the tree level is that of Rhizophora Apiculata (INP: 165.85) and the lowest is Ceriops Sp (INP: 7.14), for the sapling/sapling level the mangrove species has an important value index the highest and lowest was Rhizopora stylosa (INP : 15, 69). As for the seedling level, the species that had the highest and lowest importance value index were Rhizophora Apiculata and Rhizopora stylosa (INP : 165.85) and the lowest (INP: 15.69). It was concluded from the results that have been carried out that the Petengoran mangrove forest area can be said to be suitable for development as an ecotourism destination with the results of the analysis of the density of the mangrove vegetation showing that the dominant plant species is Rhizophora Apiculata, so that the condition of the mangrove forest in Petengoran, Padang Cermin District, is included in the condition category. good with moderate criteria, not too dense.